2021
DOI: 10.1103/physrevb.103.085204
|View full text |Cite
|
Sign up to set email alerts
|

Phonons of hexagonal BN under pressure: Effects of isotopic composition

Abstract: Raman scattering experiments on isotopically enriched hexagonal boron nitride have been performed under pressure up to 11 GPa at room temperature. The sublinear increase of the Raman-active E 2g mode frequencies has been characterized. The pressure behavior has been analyzed by means of a bond-stiffness-bond-length scaling parameter γ which takes into consideration the vast differences in a-and c-axis compressibilities. The interlayer shear mode exhibits a γ parameter similar to that of graphite, and the mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…[34] Recently, a substantial amount of theoretical work has been devoted to the calculation of phonon-assisted luminescence and optical absorption spectra in h-BN to elucidate the long-debated Stokes shift. [31,35,36] The relevance of phonons in h-BN emission and in phonon-polariton hybrid excitations [37,38] has inspired a fair amount of detailed optical studies of the h-BN phonons by means of Raman scattering [39][40][41][42][43] and infrared transmission/reflectivity measurements. [44][45][46] While ab initio calculations of the optical properties and quasiparticle electronic band structure of h-BN in the GW approximation have been available for some time, [30,32,47] experimental studies probing the optical excitations of h-BN are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Recently, a substantial amount of theoretical work has been devoted to the calculation of phonon-assisted luminescence and optical absorption spectra in h-BN to elucidate the long-debated Stokes shift. [31,35,36] The relevance of phonons in h-BN emission and in phonon-polariton hybrid excitations [37,38] has inspired a fair amount of detailed optical studies of the h-BN phonons by means of Raman scattering [39][40][41][42][43] and infrared transmission/reflectivity measurements. [44][45][46] While ab initio calculations of the optical properties and quasiparticle electronic band structure of h-BN in the GW approximation have been available for some time, [30,32,47] experimental studies probing the optical excitations of h-BN are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…12 Other reports have studied the effects of isotopes in hBN on phonon lifetime 13 and Raman response of hBN under high pressure. 14 In the work of Li et al, tuning of the lattice phonons using isotopes has been reported for 2D MoS 2 with 92 Mo and 100 Mo isotope enrichment for the first time. 15 Compared with materials containing a natural mixture of Mo isotopes, isotopically pure samples showed higher thermal conductivity, stronger photoluminescence, and longer exciton lifetime.…”
Section: Introductionmentioning
confidence: 97%
“…Temperature-dependent experiments on hBN, investigating the shear and breathing motions of adjacent layers, highlighted the unique impact of isotope engineering on vdW interactions in layered materials, offering insights into the understanding and control of vdW bonding in such materials . Other reports have studied the effects of isotopes in hBN on phonon lifetime and Raman response of hBN under high pressure …”
Section: Introductionmentioning
confidence: 99%